تطوير عمل أنظمة التحكم بأنظمة التكييف المركزية - الأيوبي محمد صالح; المصري أحمد محمود; الخطيب محمد موفق (Latakia University Journal -Engineering Sciences Series, 2014)
يعد قطاع المباني من أبرز القطاعات المستهلكة للطاقة، فبالإضافة إلى الإنارة أصبح موضوع التكييف من الضروريات في جميع المباني سواء منها السكنية أو الإدارية والخدماتية الخاصة منها أو العامة، وذلك لتوفير ظروف الراحة المناسبة للموظفين والعمال وتحسين الإنتاجية بأقل التكاليف الممكنة. يهدف هذا البحث إلى دراسة التحكم بكميات الهواء الجديد والمطرود في القاعات التدريسية والصالات الكبيرة بشكل عام ذات العدد المتغير للأشخاص المتواجدين فيها، من خلال ضبط كميات الهواء الجديد والمطرود تبعاَ لإشغاليه المكان من خلال تجهيزات تقيس كمية ثاني أكسيد الكربون في المكان المدروس وبالتالي التحكم بكمية الهواء الجديد والمطرود. تم إجراء دراسة تطبيقية واقتصادية لاستخدام نظم التحكم تلك وتم استخلاص مجموعة من النتائج والاستنتاجات. The building sector is considered one of the leading sectors in energy-consumption. In addition to lighting, heating and cooling systems have become important consumers in all buildings (both residential, administrative, and service both private and public) ensuring a comfortable environment for staff and workers and improving productivity at the lowest possible cost. This research aims to study the control quantities of fresh and exhausted air in large halls and auditoriums, where the occupancy level changes. This is done by adjusting the amount of fresh and exhausted air according to the occupancy via CO2 sensors, which measure the ratio of CO2 in the targeted places, controlling the volume of fresh and exhausted air according to the number of available people. A case study was done to use control systems; final results and conclusions have been illustrated.